2010
DOI: 10.1021/ef900868w
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Turkish Oil Shales by Electromagnetic Heating and Determination of the Dielectric Properties of Oil Shales by an Analytical Method

Abstract: The effect of microwave irradiation on the recovery of three different oil shale samples was studied. To enhance the microwave efficiency, three different iron powders (Fe, Fe 2 O 3 , and FeCl 3 ) and their three different doses (0.1, 0.5, and 1% by weight, each) were added to the samples as microwave receptors. The doses of each receptor were optimized for each oil shale sample based on the highest oil or gas production value obtained experimentally. During the experimental studies, the temperature distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…Bio-oil yields were still very low. Studied on microwave-assisted heating of three kinds of oil shales, with high ash content showed that low bio-oil yields (0-0.24 wt.%) was obtained; which were mainly caused by the high ash contents (60.5-70.9%) [122].…”
Section: Inorganicsmentioning
confidence: 99%
“…Bio-oil yields were still very low. Studied on microwave-assisted heating of three kinds of oil shales, with high ash content showed that low bio-oil yields (0-0.24 wt.%) was obtained; which were mainly caused by the high ash contents (60.5-70.9%) [122].…”
Section: Inorganicsmentioning
confidence: 99%
“…1 This way the electromagnetic radiation is converted to thermal energy. 2 The amount of heat generation varies according to the magnitude of the microwave frequency and the dielectric properties of the polar molecules which are subjected to microwave radiation. 3 The polarity of a molecule is quantified with the dipole moment of the molecule, which in turn, is determined by its molecular structure.…”
Section: Introductionmentioning
confidence: 99%
“…27,28,29 By considering all of these drawbacks of existing and commonly used emulsion breaking methods, we propose a quick, energy and cost effective solution to break emulsions. 2,30 Thus, we investigate the effectiveness of microwave heating for emulsion treatment by considering the contribution of polar components in emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…14 In the presence of water vapour and heating under microwave irradiation, the liquid products 15 yield decreased (Table 3). Table 2 shows that the total carbon content did not decrease as much 16 as when only oil shale was used, which implies lower organic matter recovery. Consequently, 17 total oil shale conversion decreased, which was found to be around 49% ( Table 4).…”
mentioning
confidence: 95%
“…The rapid 13 variation in the power level is believed to be related to the change in the loss factor (dielectric 14 loss tangent) of the sample, which may be affected by changes at the molecular or structural 15 levels of the material, such as its decomposition 45 . 16 Considering the result from Rock-Eval analysis, where Tmax was observed at 444ºC, it is 17 interesting to note the difference in the transformation temperature between both heating 18 methods. In fact, the temperature reading during microwave irradiation using the infrared 19 temperature probe is taken as an average of the sample's bed temperature.…”
mentioning
confidence: 99%